Lead from the future how to turn visionary thinking into breakthrough growth - Johnson, Mark W. (Gildan Audio, 2020)
We all know a visionary leader when we see one. They're bold and prophetic and at the same time pragmatic. They don't just promote change-they drive it, while inspiring and mobilizing others to do the same. Visionaries like Steve Jobs and Jeff Bezos possess a host of innate qualities that make them extraordinary, but what truly sets them apart is their ability to turn vision into action.In Lead from the Future, Innosight's Mark W. Johnson and Josh Suskewicz introduce a new way of thinking and managing, called "future-back," that enables any manager to become a practical visionary. Addressing the many barriers to change that exist in established organizations, they present a systematic approach to overcoming them that includes: the principles and mindset that allow leadership teams to look beyond typical short-term planning horizons; a method for turning emerging challenges into the growth opportunities that can define an organization's future; a step-by-step approach for translating a vision into a strategic plan that teams can align around and commit to; and ways to ensure that visionary thinking becomes a repeatable organizational capability. As practical as it is inspiring, Lead from the Future is the guide you and your team need to develop a vision and translate it into transformative growth.